Ideological Frames and Reaction to Intergroup Norm Violations*. (March 2023) - Tripathi, R. C.; Kumar, Rashmi; Siddiqui, Roomana N.; Mishra, R. C.; Bano, Shabana
This article examines how ideological frames, certain context factors and emotions influence choice of a retributory, retaliatory or reconciliatory reaction in intergroup conflict situations. Hindu and Muslim respondents supporting secular multiculturalism and composite culturalism gave their reactions to three norm-violating situations of varying intensities. Multinomial logistic regression was used to predict preferred reactions across situations. Reconciliation in comparison to retaliation and retribution was the most preferred reaction of both Hindus and Muslims. Ideological beliefs also predicted preferred reactions of respondents. Muslims with composite culture beliefs preferred retribution over reconciliation in two out of three situations, while Hindus having composite cultural beliefs preferred reconciliation over retaliation only in one situation. Positive out-group attitudes favoured a reconciliatory reaction in both groups. Anger and fear influenced choice of reactions of Hindus but not of Muslims. For Hindus and Muslims, resource power favoured choosing retribution over reconciliation. However, Muslims with greater retaliatory power chose retaliation. Own group identity and fraternalistic relative deprivation (FRD) played only a minor role.